Slope stability rating system - Othman, Rashidi; Hashim, Khairusy Syakirin Has-Yun; Hasni, Mohd Shah Irani (2018)
Slope Stability Rating System uses a rating scorecard index that measured 7 variables from soil physical and chemical properties of the highly weathered soil or Oxisols into a single index number. This index was developed to assess trends in slope soil stability quality index and establish baseline levels for different soil and slope types. Slope Stability Rating System is focusing on items such as: 1. Slope Profiles 2. Slope Facilities 3. Slope Soil Chemical Properties 4. Slope Soil Physical Properties 5. Slope Maintenance 6. Innovation Every item above will be rated according to the points given based on the priority. Development of Slope Stability Rating System was developed to cater for the specific demands of local road contractors and highway construction industry needs which involves the process of cutting and filling the slopes; to be implemented in any slope management industries such as highways, housing and tourism accommodation premises areas in assessing the instability of slopes or the probability of occurrence and likely severity of landslides.